The Comparison between Wattpad and Blog in Project Based Learning to Teach Written Analytical Exposition Text - Hanifah, Fahmi Millati; Bharati, Dwi Anggani Linggar (ELT Forum: Journal of English Language Teaching, 2019)
This final project was based on a research which attempts to investigate the use of wattpad and blog combined with project based learning in teaching writing skills. The purpose of the study was to find out which one is more effective between wattpad and blog in project based learning to teach written analytical exposition text. A quasi-experimental study was used as the research design in this study. The sample was the eleventh grade students of SMA Ibu Kartini Semarang that involved 26 students. They were divided into experimental group 1 and experimental group 2. The experimental group 1 was taught using wattpad while the experimental group 2 was taught using blog as the learning media and both of them used project based learning as teaching method.             The pre-test result revealed the mean score of the experimental group 1 was 60.76 and the experimental group 2 was 60.69. It meant that the two groups had similar competence before getting the treatment. The post-test mean scores of experimental group 1 and experimental group 2 were 80.23 and 74.46. The t-test of post-test showed that there was a significant difference between the experimental group 1 and the experimental group2 since t-value was higher than t-table (4.490 > 2.064).             It could be concluded that both wattpad and blog were effective as the learning media to teach writing skills. However, the use of wattpad was more effective than using blog in project-based learning to teach written analytical exposition text. Therefore, it was suggested that the teachers should consider the social media of wattpad and blog were the effective learning media in teaching writing because they allowed the students to express ideas and develop their writing skills.                Keywords: Wattpad; Blog; Project Based Learning; Writing; Analytical Exposition Text